Revelation Structures and the Search for Identity in Marc Levy’s Novels: Morphological Analysis of L’Étrange voyage de Monsieur Daldry and Une autre idée du bonheur - Adékambi, Adéchinan David (Thélème. Revista Complutense de Estudios Franceses, 2026)
This article presents a formalist and structural analysis of Marc Levy’s L’Étrange voyage de Monsieur Daldry and Une autre idée du bonheur. The study examines the narrative mechanics underlying these successful stories, which are often marginalised by academic critics because they belong to popular literature. Using a framework that combines Propp’s formalist approach and Bremond’s structuralist approach, the article highlights the existence of a stable underlying structure organised around three fundamental narrative elements: identity provocation, the initiatory quest and the final revelation. The analysis shows that the novels studied are based on a pattern of identity transformation founded on the revelation of a hidden lineage. The journey functions as a device for gradual unveiling, leading to a restorative anagnorisis that restores the unity of the subject.